Globalized Digital Marketing Strategies amid Technological Disruption: Addressing Ethical Gaps through Maqashid Sharia - Sadeli, Mochamad Sumpena; Luluk Latifah (Relevance: Journal of Management and Business, 2025)
The rapid expansion of digital marketing amid globalization and technological disruption has fundamentally transformed contemporary marketing strategies. However, prior studies largely emphasize efficiency, performance metrics, and technological capabilities, while giving limited attention to ethical accountability. This study addresses this gap by examining online marketing strategies through the lens of Islamic marketing ethics, grounded in the Maqashid Shariah framework. Using a descriptive and exploratory qualitative design, the study analyzes purposively selected secondary data from peer-reviewed international journals, industry reports, and documented digital marketing practices across global and emerging markets. Thematic analysis is employed to identify strategic patterns, ethical challenges, and value-creation mechanisms in online marketing communication. The findings indicate that online marketing has evolved into an integrated strategic system characterized by targeted communication, data-driven personalization, interactive engagement, and measurable performance outcomes. Despite these advantages, significant ethical challenges emerge, particularly regarding transparency, data responsibility, consumer autonomy, and short-term performance orientation. By applying Maqashid Shariah, the study demonstrates that ethical online marketing should protect consumer intellect, safeguard wealth, and promote social welfare. The study contributes theoretically by positioning Maqashid Shariah as a normative framework for evaluating digital marketing strategies and practically by guiding firms toward ethically responsible and sustainable digital innovation.